Establishment of a robust cloning technology for mammals - Duarte, Manoel Paulo Menna Barreto (2001)
This thesis is presented in two parts. The first part concerns production of sheep-goat hybrid embryos using oocyte in vitro maturation (IVM) and in vitro fertilization techniques. Initial experiments were carried out to optimise procedures for harvesting and maturing sheep oocytes in vitro prior to in vitro fertilisation with sheep sperm. Comparisons were made between two procedures, viz. aspiration vs sectioning, for collecting oocytes from sheep avaries obtained at a local abattoir. The aspiration procedure yielded less oocytes (average number of oocytes per ovary 1.09), compared wi th 5.18 for sectioning procedure (p<0.001). However the oocytes recovered by aspiration procedure were of better quality with more oocytes maturing in vitro to metaphase II (aspiration 95.5% vs sectioning 72.4%, p<0.001), more undergoing normal fertilisation (aspiration 71.8% vs sectioning 34.5%, p<0.001), and more showing a cleavage rate (aspiration 67.8% vs sectioning 23.3%, p<0.001). Oocytes were matured in vitro in a medium supplemented with commercial fetal calf serum. Other protein supplements were investigated including serum from a geep and a sheep/geep hybrid, but the commercial fetal calf serum proved to be the most effective. Hybrid embryos were then generated using in vivo matured goat or sheep x goat hybrid oocytes fertilised in vitro with sheep sperm. With the goat oocytes fertilised with sheep sperm, zygotes developed from the in vivo matured oocytes yielded better cleavage rates than those which were matured in vitro, (86.8% vs 48.4%, p<0.001). In contrast, in experiments with oocytes recovered from the sheep x goathybrid and fertilised with sheep sperm, zygotes from in vivo matured oocytes produced similar cleavage rates (68.4%) to the in vitru matured oocytes (50.0%; p>0.05). Blastocysts created by fertilizing goat oocytes with sheep semen were cultured in vivo. One blastocyst resulted from in vitro matuired oocytes and 12 from in vivo matured oocytes (p>0.05). The recovery rate of the blastocysts following incubation in vivo for the in vitro matured oocytes was 29.9%, and for the in vivo matured oocytes, 32.6% (p>0.05). The second part of the thesis is aimed at developing efficient procedures for generating female chimeras for use as recipients for hybrid embryos and for exploring the use of the chimeric route as a means of re-establishing the genome of an embryonic stem cell line into the germ line. Initial experiments were carried out using a mouse model with the intention of subsequently applying the technology to sheep and goat embryos. This study presents only those studies undertaken with mouse embryos. Comparison was made between various ways of creating chimeric mice, including injection of embryonic stem cells or inner cell mass cells into blastocysts and through embryo aggregation. The effects of mouse strain and time of transfer on the eff iciency of production of mouse germline chimeras was investigated. For production of chimeras from embryo stem cells, host blastocysts were obtained from three strains of mice namely (Swiss albino, C57BL/6 and CBAC57/F1) which were injected with three !ines of embryonic stem cells, namely (E14, EMBL-5 and E14 transfected). No chimeras were produced using blastocysts from C57BL/6 mice blastocysts as recipients, however chimeras were produced with blastocysts from the other two mouse strains. Altogether 925 blastocysts were injected with stem cells and transferred. These resulted in 105 offspring, of which 35 were chimeric. For production of chimeras by transferring inner cell mass cells, combinations of cells and blastocysts from Swiss albino and C57BL/6 strains were used. Only one chimera resulted from 64 embryos inoculated with inner cell mass cells and this chimera wvas produced from Swiss albino inner cell mass cells inserted into a C57BL/6 blastocyst. Swiss albino and C57BL/6 mice were also used for production of chimeras by embryo aggregation. In these experiments, 62 aggregated blastocysts were transferred, resulting in 13 offspring of which 3 were coat colour chimeras. The creation of germline chimeric individuais is widely used as a means of materialising the karyoplast genome from embryonic stem cells or inner cell mass cultures. However, it is presently only successful at low efficiency. This inefficiency would be a major constraint in the application of this technology to farm animais, due to their generally low fecundity and long intergenerational interval. These limitations could be overcome through the more direct route of using nuclear transfer technology to re-establish the genome in a germline. However, this approach requires large numbers of host cytoplasts which are prepared by surgical enucleation of activated IVM oocytes. In anticipation of the requirement for simpler, more robust procedures for preparing cytoplasts, various techniques for enucleation of recipient oocytes (mouse) and activation of the cytoplasts (ovine) have been investigated. The mouse oocytes were enucleated using centrifugation following lpcubation in cytochalasin B for 1 or 3 hours. All treatments were effective, however the best combination for enucleation was centrifugation following incubation in cytochalasin B for 3 hours. In respect to activation of sheep oocytes, four treatments were investigated. All were found capable of activating sheep oocytes, however electroactivation proved the best of the approaches used resulting in 64% of the oocytes being activated. This compared with only 35.4% for ethanol activation, using ethanol treatment. The technologies explored in this thesis are part of a study aimed at developing the advanced reproductive technologies reguired to allow multiplication of rare mammalian genotypes such as animals threatened by extinction, endangered animais or novel commercially valuable genotypes, including transgenic animals through cloning procedures.